2004
DOI: 10.1007/s11141-005-0003-z
|View full text |Cite
|
Sign up to set email alerts
|

Formation of coherent spatial structures in the reaction-diffusion atmospheric system under the action of a planetary wave

Abstract: 551.510On the example of the effect of an atmospheric wave with given amplitude on the density oscillations of minor gas constituents near the mesopause (at heights 80-90 km, we consider the influence of the quasi-resonant periodic spatial transport on a distributed system responding subharmonically to a periodic external action (diurnal sunlight variations). Numerical modeling revealed the formation of a coherent horizontal distribution of the dynamical variables (i.e., the concentrations of small constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The other studies (e.g., Kulikov, 2004, 2007; Kulikov & Feigin, 2004, 2005; Kulikov & Gashturi, 2006; Sonnemann, 2001; Sonnemann et al, 1999; Sonnemann & Feigin, 1999; Sonnemann & Grygalashvyly, 2005) concerned the influence of different types of mesospheric transport (diffusion and winds in the vertical and horizontal directions and quasi‐2‐day atmospheric waves). In particular, Sonnemann and Feigin (1999) and Sonnemann et al (1999) analyzed the influence of the vertical eddy diffusion and found that in most cases only the first nontrivial mode of behavior (oscillations with periods of 2 days) can survive at the real values of the diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The other studies (e.g., Kulikov, 2004, 2007; Kulikov & Feigin, 2004, 2005; Kulikov & Gashturi, 2006; Sonnemann, 2001; Sonnemann et al, 1999; Sonnemann & Feigin, 1999; Sonnemann & Grygalashvyly, 2005) concerned the influence of different types of mesospheric transport (diffusion and winds in the vertical and horizontal directions and quasi‐2‐day atmospheric waves). In particular, Sonnemann and Feigin (1999) and Sonnemann et al (1999) analyzed the influence of the vertical eddy diffusion and found that in most cases only the first nontrivial mode of behavior (oscillations with periods of 2 days) can survive at the real values of the diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…These waves were studied analytically by Kulikov et al (2020). With the use of 1-D and two-dimensional (2-D) models, Kulikov (2004Kulikov ( , 2007 investigated the influence of a quasi-2-day atmospheric wave on the 2DPO and revealed the possibility of spatial synchronization between the wave and the 2DPO phase distribution. It can be important from the point of view of the feedback effect of mesospheric photochemistry to wave excitation via the corresponding modulation of air photochemical heating.…”
mentioning
confidence: 99%